FREE MOVEMENT OF GOODS IN THE EUROPEAN COMMUNITY: A CRITIQUE OF THE JURISPRUDENCE ON ARTICLE 30 OF THE TREATY OF ROME - Lee, Ian (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 1993)
Article 30 of the Treaty of Rome prohibits "quantitative restrictions on imports and all measures having equivalent effect", among the Member States of the European Community. The author suggests that the excessively broad interpretation given by the European Court of Justice to the phrase "measures having equivalent effect" implies that virtually all national legislation is capable of hindering intra-Community trade. Following a discussion of the theoretical basis for the Court's reasoning, the author maintains that the inadequacy of the Court's approach became evident in a series of recent cases in which Sunday observance legislation was alleged to violate Article 30. The Court has tried to reduce the scope of Article 30 by relaxing the criteria necessary to justify a derogation from the principle of the free movement of goods. However, the author argues that the Court cannot avoid reconsidering its earlier rulings on Article 30, and that, in the interests of certainty and stability, it should do so expressly.